Ultrastructural investigation of synaptic alterations in the rat hippocampus after irradiation and hyperthermia - ERCAN, FERİHA; KAYA, ÖZLEM TUĞÇE (TAYLOR & FRANCIS INC, 2020)
This study aimed to investigate ultrastructural synaptic alterations in rat hippocampus after in utero exposure to irradiation (IR) and postnatal exposure to hyperthermia (HT). There were four groups in each of the time points (3(rd) and 6(th) months). IR group: Pregnant rats were exposed to radiation on the 17(th) gestational day. HT group: Hyperthermia was applied to the rat pups on the 10th day after their birth. IR+HT group: Both IR and HT were applied at the same time periods. Control group: No IR or HT was applied. Rat pups were sacrificed after 3 and 6 months. Thin sections from the dentate gyrus (DG) and the CA3 of hippocampus were evaluated for synapse numbers by electron microscopy. Synapses were counted, and statistical analysis was performed. Abnormalities in myelin sheath, mossy terminals and neuropil were observed in the CA3 and DG of all groups. The synapses in the CA3 region were significantly increased in the IR-3(rd) month, IR-6(th) month, and IR+HT-3(rd) month groups vs control group. Synapses were significantly increased in the DG of HT-3(rd) month group. A trend for an increase in synapse numbers was seen in the CA3 and DG. Increased number of synapses in the rat hippocampus may be due to mossy fiber sprouting, possibly caused by in utero irradiation and/or postnatal hyperthermia.
Keywords: Radiation; hyperthermia; hippocampus; synapse; ultrastructure; GRANULE CELL NEUROGENESIS; POSTISCHEMIC HYPERTHERMIA; BRAIN; ISCHEMIA; DAMAGE; REORGANIZATION; HYPOTHERMIA; SEIZURES; INJURY